The effect of data analytics quality on fintech P2P lending sustainability through operational performance as an intervening variabl - Efrizal Syofyan; Rino Dwi Putra; Muhammad Alam Mauludina; Vitra Yozi Chaniago; Junaidi Junaidi (Decision Science Letters)
This study aims to explore the effect of data analytics quality on company sustainability through operational performance as an intervening variable of Fintech Peer to Peer Lending (P2P) companies registered and licensed at the Financial Services Authority (known as OJK) Indonesia. This study is quantitative research using primary data collected through questionnaires and interviews. The data came from 104 company leaders and involved 91 Fintech P2P Lending companies registered and licensed at OJK until December 2023. Data were processed using statistical tools Structural Equation Modeling (SEM)-Lisrel. The result of processed data indicates that data analytics quality has a positive and significant effect on company sustainability through operational performance as an intervening variable. Data analytics quality with AI-based automation makes repetitive work operations easy, efficient and effective which has implications for increasing the sustainability opportunities of fintech companies.